PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENGHINAAN MELALUI MEDIA ELEKTRONIK - Dekie GG Kasenda (Jurnal Ilmu Hukum Tambun Bungai, 2018)
The Crime of Insulting Through Electronic Media is a criminal offense that attacks the right of a person in the form of damaging a person's good name / honor through social media. The offense of defamation set forth in Article 310 of the Criminal Code has the concept of criminalizing any person who orally orally attacks a person's honor by alleging something to know publicly. While the criminal acts regulated in Article 27 paragraph (3) of the Law on ITE is more assertive and criminal threats more closely than the Criminal Code. However, when viewed from the formulation of the article on defamation offense, the Criminal Code is more detailed in regulating it by distinguishing the types of humiliation, while the ITE Act seems simpler in the formulation of the article on contempt. Law enforcement against criminal act of defamation through electronic media is done through preventive and repressive efforts. Preventive efforts by conducting socialization through electronic media means integrated by the internet network, namely facebook account Police of the Republic of Indonesia; and repressive efforts that is the penal approach. Punishment for the offender of defamation through electronic media is regulated in Article 27 paragraph (3) of the Law on EIT and its criminal threat is more severe than the Criminal Code. In Article 310 Paragraph (1) of the Penal Code 9 (nine) months and Article 310 paragraph (2) of the Criminal Code of criminal offense is 1 (one) year 4 (four) months with a fine amount of four thousand five hundred rupiah. While in Article 45 paragraph (1) UU ITE maximum imprisonment of 6 (six) years and a maximum fine of 1 (one) billion rupiah.